Effect of Seed Priming and Plant Geometry on the Growth and Productivity of Emmer Wheat (Triticum dicoccum L.) - Rathod, Nagesh; Lamani, Kumar D.; Potdar, Milind; Reddy, Uday G. (International Journal of Economic Plants, 2024)
A field experiment was conducted at Research field of Ugar Khurd, Belangavi, Dharwad, Karnataka, India during rabi season of October, 2022–February, 2023 under irrigated ecosystem on deep clay soil to study the system of wheat intensification for higher productivity of emmer wheat (Triticum dicoccum L.). The experiment was laid out in split plots design with three replications. The treatments comprised of two genotypes in main plot viz., Gokak local and DDK 1029 with and without seed priming and four planting geometries in Sub-plots viz., 30×15 cm2, 45×15 cm2, 20×20 cm2 and 20 cm2 (Recommended Package of Practices). The result indicated that primed seeds recorded significantly higher grain yield (3853 kg ha-1), straw yield (6426 kg ha-1), gross returns (Rs. 1,41,915 ha-1), net returns (Rs. 92,033 ha-1) and B:C ratio (2.88) as compared to un-primed seeds. The sowing of emmer wheat in 30×15 cm2 planting geometry recorded significantly higher grain yield (4020 kg ha-1), straw yield (6630 kg ha-1), gross returns (Rs. 1,47,989 ha-1), net returns (Rs. 1,01,742 ha-1) and B:C ratio (3.20) as compared other planting geometries. The combination of primed seeds sown with 30×15 cm2 planting geometry recorded significantly higher grain yield (4413 kg ha-1), straw yield (7064 kg ha-1), gross returns (Rs. 1,62,240 ha-1), net returns (Rs. 1,15,828 ha-1) and B:C ratio (3.50) as compared to other treatment combinations.